2019
DOI: 10.1186/s12263-019-0628-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of food intake for nuts and vegetable oils: an extensive literature search

Abstract: Nuts and vegetable oils are important sources of fat and of a wide variety of micronutrients and phytochemicals. Following their intake, several of their constituents, as well as their derived metabolites, are found in blood circulation and in urine. As a consequence, these could be used to assess the compliance to a dietary intervention or to determine habitual intake of nuts and vegetable oils. However, before these metabolites can be widely used as biomarkers of food intake (BFIs), several characteristics h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 197 publications
(252 reference statements)
2
54
0
1
Order By: Relevance
“…However, our data indicated that only nut consumption significantly increased over the intervention with MD. Therefore, increase in urinary urolithin glucuronides was most likely attributed to the intake of walnuts in our study as previously reported by others 50. Recently, urolithin A has been shown to improve intestinal barrier function in a preclinical model51 and has also been associated with lower cardiometabolic risk 52.…”
Section: Discussionsupporting
confidence: 88%
“…However, our data indicated that only nut consumption significantly increased over the intervention with MD. Therefore, increase in urinary urolithin glucuronides was most likely attributed to the intake of walnuts in our study as previously reported by others 50. Recently, urolithin A has been shown to improve intestinal barrier function in a preclinical model51 and has also been associated with lower cardiometabolic risk 52.…”
Section: Discussionsupporting
confidence: 88%
“…Since nuts are sources of fats and a wide variety of micronutrients and phytochemicals, after ingestion, several of their constituents, as well as their derived metabolites, are found in the bloodstream and urine. These molecules appear to serve as markers of nut intake, where α-linolenic acid, urolithins, and 5-hydroxyindole-3-acetic acid appear to be markers of walnut intake, α-tocopherol and catechin-derived metabolites appear to be markers of almond intake, and selenium marks Brazil nut consumption [22].…”
Section: Nuts and Other Metabolitesmentioning
confidence: 99%
“…In addition to their high content of polyunsaturated fatty acids (PUFA) and monounsaturated fatty acids (MUFA), phytochemicals, dietary fibers, magnesium, L-arginine, and antioxidants compose these foods. Together, these nutrients act by modulating the intestinal microbiota [20,21] and are precursors of a series of metabolites [22,23]. In addition, nut consumption is inversely associated with the incidence of CVD, coronary artery disease (CAD), atrial fibrillation, as also with CVD mortality, CAD mortality, and stroke mortality [24].…”
Section: Introductionmentioning
confidence: 99%
“…Another important issue to consider is the presence of confounding factors such as consumption of other foods rich in ellagitanins and anthocyanins. Special attention should be put on nut intake, as these are a well-known source of ellagitannins [ 58 ]. Regarding anthocyanin intake, among vegetables and fruits, red radish, red cabbage, black beans, eggplants, grapes, pomegranate, and cherries represent likely confounding factors [ 104 ].…”
Section: Discussionmentioning
confidence: 99%